Internalization of Educational Values in the Founding Family of the Pesantren: A Case Study of Agency and Structure in SPMAA - Muchtar, Gema Diena Titisan; Dayati, Umi; Purwito, Lasi (Universitas Negeri Padang, 2025)
Pesantren play a strategic role in shaping students' character through family-based education. The Sumber Pendidikan Mental Agama Allah (SPMAA) Foundation, founded by MA Muchtar, serves as an example of how educational values are internalized within the pesantren environment. This study aims to describe MA Muchtar's behavior in instilling the pesantren's vision, analyze the family educational values he passed down, and evaluate their impact on his children and students. This research employs a qualitative approach using a case study method, with data collected through in-depth interviews, observations, and document analysis. The findings indicate that MA Muchtar demonstrated three key behaviors in educating: simplicity, discipline, and role modeling. The primary family educational values transmitted include monotheism, humanity, simplicity, lifelong education, communication and honesty, as well as harmony and unity. These values are internalized through direct role modeling, habituation, and daily activities within the family and pesantren environment. This study emphasizes the significance of individual agency in shaping and transmitting educational values within the pesantren’s social structure.